Sunday kind of love [large type] - Garlock, Dorothy (Thorndike Press, A part of Gale, Cengage Learning, 2016)
"Buckton, Indiana, 1956. As post-war America brims with new opportunities, a young woman discovers the courage to follow her dreams-and her heart. Gwendolyn Foster's life seems like a dream come true. A bright future in front of her, the successful, traditional man her parents wanted at her side. What more could a girl ask for? But Gwen has a different dream altogether-to be a writer-and she won't rest until it comes true. Strong arms to support her, not own her. that's what she needs. And she finds them in the most unexpected of places. Hank Ellis has long been haunted by his little brother's death. He knows the entire town blames him for the accident, but it's only fitting. He blames himself too. So he's shocked when Gwen ignores the vicious gossip and befriends him. And before long, everything changes for them. Folks warn Gwen about Hank, but she knows in her heart that they're wrong. Drawn to this man of bravery and kindness who encourages her to pursue her passions, Gwen can finally envision the life she's always wanted. And with Gwen, Hank finds the strength to let go of his guilt, as he dares to hope for a future with her. But braving the town that turns against them isn't the only challenge they face. For Hank still harbors a dark secret, a shocking truth that may force him to lose Gwen forever"--